Thermal Emission of Alkali Metal Ions from Al30-Pillared Montmorillonite Studied by Mass Spectrometric Method - V. B. Motalov; N. S. Karasev; N. L. Ovchinnikov; M. F. Butman (Journal of Analytical Methods in Chemistry)
The thermal emission of alkali metal ions from Al30-pillared montmorillonite in comparison with its natural form was studied by mass spectrometry in the temperature range 770–930 K. The measurements were carried out on a magnetic mass spectrometer MI-1201. For natural montmorillonite, the densities of the emission currents (j) decrease in the mass spectrum in the following sequence (T = 805 K, A/cm2): K+ (4.55 · 10−14), Cs+ (9.72 · 10−15), Rb+ (1.13 · 10−15), Na+ (1.75 · 10−16), Li+ (3.37 · 10−17). For Al30-pillared montmorillonite, thermionic emission undergoes temperature-time changes. In the low-temperature section of the investigated range (770–805 K), the value of j increases substantially for all ions in comparison with natural montmorillonite (T = 805 K, A/cm2): Cs+ (6.47 · 10−13), K+ (9.44 · 10−14), Na+ (3.34 · 10−15), Rb+ (1.77 · 10−15), and Li+ (4.59 · 10−16). A reversible anomaly is observed in the temperature range 805–832 K: with increasing temperature, the value of j of alkaline ions falls abruptly. This effect increases with increasing ionic radius of M+. After a long heating-up period, this anomaly disappears and the lnj-1/T dependence acquires a classical linear form. The results are interpreted from the point of view of the dependence of the efficiency of thermionic emission on the phase transformations of pillars.